Stereoselective synthesis of fluoroalkylated (Z)-alkene via nickel-catalyzed and iron-mediated hydrofluoroalkylation of alkynes - Li, Xiang-Rui; Li, Wen-Xin; Zhang, Zhuo-Wen; Shen, Chuanji; Zhou, Xiaocong; Chu, Xue-Qiang; Rao, Weidong; Shen, Zhi-Liang (ORGANIC CHEMISTRY FRONTIERS, 2021)
An efficient nickel-catalyzed, iron-mediated hydrofluoroalkylation of alkynes with bromodifluoroacetate or perfluoroalkyl iodide was developed. The reactions proceeded efficiently via a radical reaction pathway to give fluoroalkylated (Z)-alkenes in moderate to good yields with good control of stereoselectivity (up to 99 : 1 Z/E), exhibiting both wide substrate scope and broad functional group tolerance. In addition, the method also entailed the easy functionalization of alkyne-tethered complex molecules derived from sugars and pharmaceuticals.